PERSEPSI SISWA DALAM STUDI PENGARUH DARING LEARNING TERHADAP MINAT BELAJAR IPA - Sobron A.N, Bayu, Rani, Meidawati (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2019)
Daring Learning provides effective learning methods, such as practicing with the existence of relevant feedback, combining collaborative activities with independent learning. Learning in the classroom with a combination of online learning gives students more interest. This study aims to develop a study of the influence of Daring Learning on the interest in learning science of grade VI students at third Elementary School of Karanglo Tawangmangu. This research method consist 26 students using quasi-experimental methods (Quasi Experiments), the population divided into 2 classes including class VI A with 13 students and class VI B with 13 students. Sampling taken in class VI A as the experimental class and class VI B as the control class. The results showed that the learning process using the Daring Learning method especially in science at third Elementary School of Karanglo Tawangmangu had used interesting media, concluding that Daring Learning-based interactive learning media, students were increasingly enthusiastic and not boring especially in learning science using the Daring Learning method. Based on the research stated on the questionnaire responses of students with Daring Learning, it shows that the cateralization is agrees to allow Daring Learning method in third Elementary School of Karanglo Tawangmangu.